(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to review the role of Virtual Reality (VR) in reducing anxiety in hemodialysis patients. The research method used is a literature review of articles published between 2020 and 2025, obtained through the Scopus, PubMed, ProQuest, and EBSCO databases. The results of the survey indicate that Virtual Reality is an innovative intervention that is effective in reducing anxiety before and during hemodialysis procedures. Of the various approaches reviewed, NefroVR is the most effective method because it not only reduces anxiety and depression through visual stimulation and VR interaction but also integrates physical activity during the procedure. This approach is more comprehensive than other VR methods, such as VR mindfulness, which focuses on relaxation; VR pain distraction, which is short-term; and VR exposure therapy, which only targets anxiety. In addition, VR-based physical training also helps improve patients’ overall quality of life. In conclusion, virtual reality has the potential to be an effective intervention method for reducing anxiety in hemodialysis patients. A 5–6 minute virtual reality session has been shown to have positive effects before and during invasive procedures in the hemodialysis room. Keywords: Hemodialysis, Anxiety, Virtual Reality